Microscopy of oxidation proceedings of the first international conference held at the University of Cambridge, 26-28 March 1990 - Bennett, M. J. 1933-; Lorimer, G. W. (Book (Institute of Metals), 1991)
Covers the reaction processes from oxide failure nucleation, through scale growth, as well as the possibilities of alloy design for improved oxidation resistance using a wide range of microscopical techniques.